Evaluation of efficacy of photodynamic disinfection against enterococcus faecalis and compare it with the effect of different endodontic irrigant activation techniques. - Amanda George Haskiyal; Dara Hamarashid Saeed (Erbil Dental Journal)
Background and objective: The aim of this in vitro study was to assess the efficacy of photodynamic disinfection against Enterococcus faecalis, and compare it with the effect of different endodontic irrigant activation techniques. Methods: Fifty single-rooted premolars with single canals were chosen for the study. Five teeth were chosen to serve as the negative control group. The remaining samples were infected with normal Enterococcus faecalis strains. They were then randomly separated into five groups, with nine teeth serving as a positive control group (E. Cont.). Each group consisted of 9 samples based on the kind of irrigant activation: E.A (Diode laser), E.B (Ultrasonic), E.C (conventional), and E.D (FotoSan®). The ProTaper NEXT rotary system up to model X3 was used to prepare all samples. For each group, 5.25% NaOCl was injected as an initial irrigant with a 30G double-side vented syringe needle, followed by 17% EDTA, then activated with NaOCl as a final irrigant. CFU of each sample was counted before and after irrigation regime, and they were compared to the control group. The efficiency of the disinfection techniques was determined using scanning electron microscopes (SEM). Result: The quantity of bacterial colony counting revealed that the control group had the largest mean of a bacterial colony (135.56±50.58); while the FotoSan group had the lowest colony mean number (23.11±9.82). SEM results indicated that the FotoSan group (5.56±3.16) and Diode laser (5.56±3.57) had the lowest surviving colony mean number. Conclusion: As an additional method, photodynamic therapy may increase the disinfection capacity of traditional endodontic treatment against E. faecalis in the root canal.